2019
DOI: 10.1093/toxsci/kfz081
|View full text |Cite
|
Sign up to set email alerts
|

Antidotal Effects of the Phenothiazine Chromophore Methylene Blue Following Cyanide Intoxication

Abstract: Our study was aimed at (1) determining the efficacy of the dye methylene blue (MB), following a rapidly lethal cyanide (CN) intoxication in un-sedated rats; (2) clarifying some of the mechanisms responsible for the antidotal properties produced by this potent cyclic redox dye. Sixty-nine awake rats acutely intoxicated by CN (IP, KCN 7 mg/kg) received saline, MB (20 mg/ kg) or hydroxocobalamin (HyCo, 150 mg/kg) when in deep coma. Survival in this model was very low, reaching 9% at 60 min without any treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 95 publications
0
23
0
Order By: Relevance
“…43 As a medical therapeutic, MB is FDA approved for the treatment of methemoglobinemia and has also shown efficacy in treating hypoxia, hypotension, and cyanide intoxication. [44][45][46][47] MSG is metabolized to alphaketoglutarate, a substrate of the citric acid cycle that would bypass the aconitase blockade following 1080 poisoning. By supporting glutamine metabolism, MSG may circumvent the bottleneck in the citric acid cycle that prevents pyruvate oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…43 As a medical therapeutic, MB is FDA approved for the treatment of methemoglobinemia and has also shown efficacy in treating hypoxia, hypotension, and cyanide intoxication. [44][45][46][47] MSG is metabolized to alphaketoglutarate, a substrate of the citric acid cycle that would bypass the aconitase blockade following 1080 poisoning. By supporting glutamine metabolism, MSG may circumvent the bottleneck in the citric acid cycle that prevents pyruvate oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 We have recently revisited the effects of MB, which was briefly proposed in the 1930s [19][20][21][22] as a treatment of CN intoxication, and found that this molecule exerts potent antidotal effects against CN toxicity through a unique modality of action that results from its distinctive cyclic redox properties. [23][24][25] These properties are currently used to treat the excessive formation of ferric iron in hemoglobin (methemoglobin), restoring the ability of hemoglobin to carry O 2 in patients with methemoglobinemia. 17,18,26,27 After being administrated, MB is immediately reduced into its leucoform, leucomethylene blue (LMB), 28 by reducing agents present in blood and cells, such as NAD(P)H. 29 reoxidized into MB by molecules with a higher redox potential (such as O 2 or most metallocompounds), giving up to two electrons in the process (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…29 Diffusing rapidly into the cytoplasm and in the mitochondria of any cells, including neurons, 30 the MB/LMB couple can restore the TCA cycle and the glycolytic activity by oxidizing NADH and decreasing the NADH/NAD ratio, 31 rescuing the TCA cycle when inhibited by the accumulation of NADH, like for instance during an impediment of the electron chain activity by CN or H 2 S intoxication. 25,28 The reestablishment of the TCA cycle can, in turn, lead to the production of ATP via succinyl-CoA synthase-the mitochondrial substrate-level phosphorylation 31 independently of the integrity of the mitochondrial ATPase activity. Also, MB/LMB redox properties appear to be able to restore the mitochondrial membrane potential, depressed by CN, through mechanisms that are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations